2017
DOI: 10.3390/ijerph14060600
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions on Hurricanes: Evidence from the U.S. Stock Market

Abstract: This article examines the market reaction of the main Property and Casualty (P & C) insurance companies listed in the New York Stock Exchange (NYSE) to seven most recent hurricanes that hit the East Coast of the United States from 2005 to 2012. For this purpose, we run a standard short horizon event study in order to test the existence of abnormal returns around the landfalls. P & C companies are one of the most affected sectors by such events because of the huge losses to rebuild, help and compensate the inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…First, we add to the growing literature on the role that public health threats play in market reactions. Prior studies contend that the firms in heavy-polluting industries have a negative market reaction to the passage of the Environmental Protection Tax Law [ 39 ]; negative cumulative abnormal returns occur during short windows around pollution events [ 38 ]; and insurance firms have higher abnormal returns around the event window in most of the hurricane hazards [ 37 ]. These findings suggest that the increase in public health risks affects the markets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we add to the growing literature on the role that public health threats play in market reactions. Prior studies contend that the firms in heavy-polluting industries have a negative market reaction to the passage of the Environmental Protection Tax Law [ 39 ]; negative cumulative abnormal returns occur during short windows around pollution events [ 38 ]; and insurance firms have higher abnormal returns around the event window in most of the hurricane hazards [ 37 ]. These findings suggest that the increase in public health risks affects the markets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Third, several studies show that event risks (e.g., pollution events, hurricane disasters) will have a negative effect on firm valuation [ 37 , 38 , 39 ]. Moreover, Liu et al [ 40 ] emphasize that significant events lead to abrupt changes in stock prices and volatility, and investors are more likely to hold less risky assets.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The current study adopted the psychological measurement paradigm of Slovic [ 47 ], which suggests that disaster risk perception is a multi-dimensional concept. With consideration to the actual research area of China, and with reference to the measurement of risk perception in the studies by the authors of [ 10 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], this study measured risk perception with respect to the following three dimensions, namely, possibility, worry, and controllability ( Table 3 ). Before the factor analysis, Cronbach’s alpha reliability tests were carried out for each measure of risk perception.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar vein, Ref. [36] found that P/C insurers were, in terms of cumulative average abnormal returns from 10 days before to 10 days after hurricane landfall, insensitive to Hurricanes Katrina (2005) and Sandy (2012). These empirical findings are consistent with other studies of the impact-both immediate and subsequent-of Hurricane Katrina, highlighting that the short-term economic impact was small and perhaps suggesting that investors do not "overreact" to hurricanes.…”
Section: Financial Resilience In a Larger Contextmentioning
confidence: 80%